(untitled) (مجلة إحالات, 2026)
In educational matters, the methodological evolution techniques, processes and mechanisms is of utmost relevance. From a didactic point of view, it is not only important to know the main teaching approaches and methods that have existed over time, but also to be aware of the current methodological paradigm. The current proposal for language teaching consists in abandoning the optimization paradigm and moving towards an adaptation paradigm. This paradigm gave birth to the flipped classroom, as a new method of learning to adapt it to current needs. Following this pedagogical model, the traditional learning roles are modified according to the expression “homeless on sand home work in class” using new technologies. The main objective of this method is to create a more active and interactive environment in the classroom and to guide learning towards action. We plan, through this study, to shed some clarity on this new pedagogy, which ends up digits place in a hybrid education at the Algerian university.